2017
DOI: 10.1111/wrr.12582
|View full text |Cite
|
Sign up to set email alerts
|

Lull pgm system: A suitable technique to improve the regenerative potential of autologous fat grafting

Abstract: Autologous fat grafting and methods of purification of harvested tissue have become one of the most current themes in regenerative medicine. The aim of this study was to evaluate the in vitro regenerative potential of abdomen lipoaspirates subjected to a combined washing-decantation purifying procedure, the Lull pgm System (Lull). Blood cells and stromal-vascular fraction (SVF) cells contained in the aspirates were investigated and compared with those obtained through more conventional fat-processing methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Most of the included studies were low level evidence (Table 2) [12, 16–18, 20, 24, 27, 29, 42, 61, 63, 65, 66, 75, 77] 11 were Level 5 [12, 16, 17, 20, 27, 42, 61, 63, 66, 75, 77] (descriptive laboratory studies), one was Level 4 [18] and only three were Level 2 [24, 29, 65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included studies were low level evidence (Table 2) [12, 16–18, 20, 24, 27, 29, 42, 61, 63, 65, 66, 75, 77] 11 were Level 5 [12, 16, 17, 20, 27, 42, 61, 63, 66, 75, 77] (descriptive laboratory studies), one was Level 4 [18] and only three were Level 2 [24, 29, 65].…”
Section: Resultsmentioning
confidence: 99%
“…All included studies [12, 16–18, 20, 24, 27, 29, 42, 61, 63, 65, 66, 75, 77] disclosed whether they had any financial or other competing interests. 73.3% ( n = 11/15 [12, 17, 20, 24, 27, 29, 42, 61, 63, 66, 77]) gave a clear objective which reduced the risk of outcome bias.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the graft should be gently washed and/or contaminates should be further removed through centrifugation. Recently Morselli et al 15 19 and Zhu et al 20 reported two closed systems for fat washing with decantation and centrifugation, showing that their procedures achieved the best balance between purification and amount of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since our study is an evolution of the fat washing technique proposed by Morselli et al, it was deemed unnecessary to demonstrate the quality and survival rate of the transferred fat. Indeed, Morselli et al 15 19 has already outlined that his technique rendered good fat survival rates. Decantation caused no harm to mature adipocytes and preserved an elevated amount of ADSCs among all the SVF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation